Effect of insulating existing houses on health inequality: cluster randomised study in the community. Issue 7591 (26th February 2007) - Howden-Chapman, Philippa; Matheson, Anna; Crane, Julian; Viggers, Helen; Cunningham, Malcolm; Blakely, Tony; Cunningham, Chris; Woodward, Alistair; Saville-Smith, Kay; O'Dea, Des; Kennedy, Martin; Baker, Michael; et al.
Abstract : Objective To determine whether insulating existing houses increases indoor temperatures and improves occupants' health and wellbeing. Design Community based, cluster, single blinded randomised study. Setting Seven low income communities in New Zealand. Participants 1350 households containing 4407 participants. Intervention Installation of a standard retrofit insulation package. Main outcome measures Indoor temperature and relative humidity, energy consumption, self reported health, wheezing, days off school and work, visits to general practitioners, and admissions to hospital. Results Insulation was associated with a small increase in bedroom temperatures during the winter (0.5°C) and decreased relative humidity (−2.3%), despite energy consumption in insulated houses being 81% of that in uninsulated houses. Bedroom temperatures were below 10°C for 1.7 fewer hours each day in insulated homes than in uninsulated ones. These changes were associated with reduced odds in the insulated homes of fair or poor self rated health (adjusted odds ratio 0.50, 95% confidence interval 0.38 to 0.68), self reports of wheezing in the past three months (0.57, 0.47 to 0.70), self reports of children taking a day off school (0.49, 0.31 to 0.80), and self reports of adults taking a day off work (0.62, 0.46 to 0.83). Visits to general practitioners were less often reported by occupants of insulated homes (0.73, 0.62 to 0.87). Hospital admissions for respiratory conditions were also reduced (0.53, 0.22 to 1.29), but this reduction was not statistically significant (P=0.16). Conclusion Insulating existing houses led to a significantly warmer, drier indoor environment and resulted in improved self rated health, self reported wheezing, days off school and work, and visits to general practitioners as well as a trend for fewer hospital admissions for respiratory conditions.